Liver Transplantation Studies Using a Canine Model: A Zoom on the Intermediate Filaments of the Cytoskeleton of the Hepatocytes - Consolato M. Sergi (Highlights on Medicine and Medical Research Vol. 9, 2021)
Acute and chronic liver failure can be tackled using liver transplantation. Graft dysfunction is still a challenge in 21st century. It affects up to one-third of the recipients, notwithstanding good to excellent long-term outcome have been reported. At the time of the writing of this chapter, the etiologic investigation of the organ dysfunction has revealed a multifactorial background. Despite the multifactorial causes, ischemia and reperfusion (I/R) injury is probably the most important contributing factor for organ dysfunction. Cholestasis, i.e., the stoppage or reduction of bile flow with or without bile duct loss or ductopenia and biliary ductular proliferations are frequent accompanying factors in I/R injury. However, they can be misleading, and they can also be present in other graft dysfunction conditions. Biliary marker levels increase usually as early as 5 days after transplantation. In this chapter, we reviewed a liver transplantation model as I/R injury model to study in detail the intermediate filaments of the cytoskeleton. We indicate that the phenotypic switch of the hepatocytes occurs earlier than frank cholestasis. We suggest that targeting this phenotypical switch of the liver cells may contribute to the savage or better outcome of the liver graft.